2002
DOI: 10.1023/a:1016330802348
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although several studies have investigated the occurrence of medical and neurological conditions in persons with autism, relatively few reports have focused on the phenomenology and treatment of psychiatric disorders in this population. There is emerging evidence that depression is probably the most common psychiatric disorder that occurs in autistic persons. In this review, we examine the factors that influence the presence of depression in this population, such as the level of intelligence, age, gender, asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(131 citation statements)
references
References 53 publications
5
123
0
3
Order By: Relevance
“…For example, depression was the most common affective difficulty in Wing's original sample of adults with Asperger syndrome (Wing 1981). Ghaziuddin and colleagues have also noted high rates of depression in their work with individuals with ASD (Ghaziuddin et al 2002(Ghaziuddin et al , 1998. As Howlin (2000) notes in her review of adult outcomes in Asperger Syndrome and ''able'' individuals with autism, by far the most common psychiatric diagnosis was depression, often associated with severe anxiety, with this representing over a third of the reported psychiatric diagnoses in the studies reviewed (Howlin 2000, p. 74).…”
Section: Introductionmentioning
confidence: 99%
“…For example, depression was the most common affective difficulty in Wing's original sample of adults with Asperger syndrome (Wing 1981). Ghaziuddin and colleagues have also noted high rates of depression in their work with individuals with ASD (Ghaziuddin et al 2002(Ghaziuddin et al , 1998. As Howlin (2000) notes in her review of adult outcomes in Asperger Syndrome and ''able'' individuals with autism, by far the most common psychiatric diagnosis was depression, often associated with severe anxiety, with this representing over a third of the reported psychiatric diagnoses in the studies reviewed (Howlin 2000, p. 74).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, having a diagnosis of ASD may in some cases further exacerbate other problems, making it harder to cope. This is particularly important to examine in more detail in light of the vast literature exploring the common co-morbidities which frequently present in individuals with ASD, most notably, mood disorders such as depression and anxiety (e.g., Ghaziuddin, Ghaziuddin, & Greden, 2002;Hammond & Hoffman, 2014;Matson & Williams, 2014;Moss, Howlin, Savage, Bolton, & Rutter, 2015;Bruggink, Huisman, Vuijk, Kraaij, & Garnefski, 2016), and behavioral disorders such as attention-deficit/hyperactivity disorder (ADHD) (e.g., Chen et al, 2015;Taylor, Charman, & Ronald, 2015;Antshel, Zhang-James, Wagner, Ledesma, & Faraone, 2016). Such comorbidities may further intensify an individual with ASD's impaired ability to cope with problems in his or her life.…”
Section: Discussionmentioning
confidence: 99%
“…Depression can often arise with an increase of withdrawal and aggressive behaviours: these symptoms may present more clearly in patients with HFA/AS, rather than in low-functioning autism (LFA), which could primarily presenting withdrawal and aggression. From other studies has been reported a very broad range of prevalence of mood disorders, from 6% up to 70% [4,5,[15][16][17][18][19]. This variability could depend to the fact that some authors examined only AS patients, other ones considered depressive symptoms rather then a diagnosis of major depression.…”
Section: Discussionmentioning
confidence: 99%